Asymmetric Information Mitigation in Supply Chain: A Systematic Literature Review - Teniwut, Wellem Anselmus; Betaubun, Kamilius D; Marimin, Marimin; Djatna, Taufik (International Journal of Supply Chain Management, 2018)
With the level of competition and consumer demand is changing rapidly, the speed and accuracy of the information flow in the supply chain increasingly necessary. Sharing of information between the parties in a supply chain plays an important role in improving the sustainability of a business, but imperfection information is inevitable because each party in the supply chain has a different objective. This condition increases the importance of a research on the mitigation of asymmetric information in the supply chain, therefore the purpose of this study was to conduct a review of previous studies related to overcoming the asymmetric information and map research trend on mitigating asymmetric information in the supply chain. We used systematic literature review (SLR) methods to analyze the data collected from Web of Science and Scopus database from 2005 to 2016. The results of this study can be used as a guide and a reference for further research related to overcoming the asymmetry of information in the supply chain in every industrial sector.